Methods of Legal Guidance for Children Who Are Not Legally Capable at the Maros Special Children's Development Institution II: Analysis of Madhab Fiqh - Pratiwi, Annisa Intan; Aisyah, Nur; Laman, Ilham (Shautuna: Jurnal Ilmiah Mahasiswa Perbandingan Mazhab, 2024)
This research discusses the implementation of legal training methods for children who are not legally proficient at the special children's training institution II Maros, then detailed into several research sub-problems, namely: 1) What is the concept of legal training methods for children who are not yet legally proficient at the Special Children's Development Institute II Maros according to the school of jurisprudence 2) What are the standards of legal education for children who are not legally competent at the special children's institution II Maros according to the school of jurisprudence. 3) What is the impact of legal training on children who are not yet legally proficient at the Special Children's Development Institute II Maros according to the school of jurisprudence. This type of research is included in field research, namely research carried out directly at the object, especially in an effort to collect data and various information. The results of these findings show that: 1) the concept of training methods applied by the II Maros Children's Special Development Institute is divided into 3, including: Independence Development. Religious Development and Skills Development 2) According to Imam Syafi', children who are not legally competent are trained by providing education and teaching. Meanwhile, according to Imam Maliki, children who are not yet legally competent are fostered by providing advice and guidance. 3) According to Imam Syafi'i, applying coaching methods to children who are not yet proficient by providing education and teaching has a good impact so that children can understand and practice Islamic teachings. Meanwhile, according to Imam Maliki's opinion, the application of coaching methods to children who are not legally competent by providing advice and guidance has a good impact. The implication of the research is that the application of training methods to children who are not yet legally proficient still provides advice training methods but is done gently so that children can easily accept them in accordance with the Imam Maliki school of thought and knowledge development training methods should be given learning in the form of providing basic material so that the children being coached receive educational simulations. the same as the level of education in public schools.